PENGEMBANGAN KURIKULUM PENDIDIKAN KESETARAAN - Sutjipto Sutjipto (JIV-Jurnal Ilmiah Visi, 2016)
The purpose of this research is to reveal how policy-makers and curriculum developers to design educational curriculum equality. This type of research is qualitative descriptive. The main data were collected by questionnaires and group discussions terpumpun. Data were analyzed using descriptive statistics, namely the depiction of the data with the pattern description. The study was conducted in November 2015 until June 2016, with a sample of teachers and education staff of three learning centers. The results showed. First, policy makers and developers are still putting that designing and realizing equality education curriculum has not made a top priority, but are waiting for formal education first. Second, policy makers and developers have not presenting concrete policy markers related complexity and context of the fundamental aspects of reality which represents the common interests of citizens of the nation that terejawantahkan in the curriculum as a tool tread life. Third, the design of educational curricula equality has not equip knowledge and competence as a prerequisite to work and also not strong attitudes toward integrity, hard work, discipline, mutual cooperation, independence, nationalism and specialized skills to solve the problem of life. Fourth, equal education curriculum design not describe the instruments to face the problem of dropouts and solve socio-economic problems oriented towards life skills in order to enter the life.